CLINICAL OUTCOME OF TWO COMPOUD CONDENSABLE RESINS FOR POSTERIOR RESTAURATION - Lahoud Salmen, Victor (2004)
The objective of the present investigation was to evaluate the clinical value of the Class I and Class H restorations. 80 bicuspids and molars with caries lessions and with reversible pulp syntomatology were divided into 2 groups: Grupo I: 40 condensed resing restorations A and group II with condensed resin B. Then, after 12 months of clinical evaluation, results showed color, marginal stained anatomic form, surface texture, marginal adaptation, secondary caries and sensitivity had 100% success in 80 treated cases.